INFORMATION MODEL OF THE MONITORING PROCESS OF HUMAN HEALTH INDICATORS - Нагога, Олександр; Лавтербах, Андрій; Штефура, Юлія; Шевченко, Костянтин (Modern engineering and innovative technologies, 2023)
In modern conditions in Ukraine, the task of introducing the latest information and measurement technologies in the system of medical care for the population is urgent. One of the possible ways to improve the quality of medical care is the use and implem